THE IMPLEMENTATION OF BUILDING WORDS IN IMPROVING VOCABULARY MASTERY OF THE SECOND GRADE STUDENTS OF SMPN 1 MAJAULENG - Mellyana Mellyana; Rizka Indahyanti; Muthmainnah Mursidin (ADHILINGUA: Journal of Language Education, Lilnguistics and Literature, 2024)
This study evaluates the effectiveness of the Building Words method in enhancing vocabulary mastery among second-grade students at SMPN 1 Majauleng. Employing a pre-experimental one-group pretest-posttest design, the research involved 30 randomly selected students. Data were collected through pretest and posttest, with an intervention using the Building Words method between the two tests. Results show a significant improvement in students' average vocabulary scores, from 31 in the pretest to 91 in the posttest. Statistical analysis using paired t-test yielded a t-value of -81.168 with a p-value of 0.000, confirming the method's effectiveness. Students' ability classification shifted dramatically from "Very Poor" and "Poor" to "Good" and "Very Good". The Building Words method proved effective in enhancing vocabulary mastery through active student engagement, collaborative learning, and a multi-sensory approach. This research highlights the potential of the Building Words method for integration into language teaching curricula and adaptation to various educational contexts. While focusing on short-term effects, the results indicate potential long-term positive impacts on students' language abilities. Further studies are recommended to evaluate long-term vocabulary retention and the application of this method in other language skills.